The solar proxy κ1 Cet and the planetary habitability around the young Sun. Issue Volume 12:Issue S328(2016) (12th September 2017) - do Nascimento, J.-D.; Vidotto, A. A.; Petit, P.; Folsom, C.; de Mello, G. F. Porto; Meibom, S.; Abrevaya, X. C.; Ribas, I.; Castro, M.; Marsden, S. C.; Morin, J.; Jeffers, S. V.; et al.
Abstract: Among the solar proxies, κ 1 Cet, stands out as potentially having a mass very close to solar and a young age. We report magnetic field measurements and planetary habitability consequences around this star, a proxy of the young Sun when life arose on Earth. Magnetic strength was determined from spectropolarimetric observations and we reconstruct the large-scale surface magnetic field to derive the magnetic environment, stellar winds, and particle flux permeating the interplanetary medium around κ 1 Cet. Our results show a closer magnetosphere and mass-loss rate 50 times larger than the current solar wind mass-loss rate when Life arose on Earth, resulting in a larger interaction via space weather disturbances between the stellar wind and a hypothetical young-Earth analogue, potentially affecting the habitability. Interaction of the wind from the young Sun with the planetary ancient magnetic field may have affected the young Earth and its life conditions.